The nature and emotional valence of a prime influences the processing of emotional faces in adults and children. (November 2018) - Conte, Stefania; Brenna, Viola; Ricciardelli, Paola; Turati, Chiara
A large body of research has investigated both the emotional elaboration of facial stimuli in adults and the development of children's recognition of emotional expressions. Yet, it is still not clear whether children's ability to recognize an emotional face may be modulated by prior exposure to a different face, and whether an emotional expression may exert an effect on the processing of subsequently encountered facial emotional expressions. We tested in three experiments the recognition of happy and angry target faces preceded by neutral faces or objects (Experiment 1) and happy or angry faces (Experiment 2A and Experiment 2B) using an affective priming task in adults and 7- and 5-year-old children. Results showed a standard prime effect for neutral faces (Experiment 1) for all participants, and for happy faces in children (Experiment 2A) and adults (Experiment 2B). Otherwise, angry faces elicited negative priming effects in all participants (Experiment 2A). Overall, our findings showed that both prior exposure to a face per se and the emotional valence of the prime face have an impact on subsequent processing of facial emotional information. Implications for emotional processing are discussed.